The Satirical Language Style and Critical Reasoning Values in the YouTube Video 'Santoon TV' and Their Relevance to the Learning of Anecdotal Texts for Class X: Gaya Bahasa Satire dan Nilai Bernalar Kritis dalam Video YouTube “Santoon TV” serta Relevansinya pada Pembelajaran Teks Anekdot Kelas X - Intan Wulan Sari; Deby Luriawati Naryatmojo (Universitas Negeri Semarang, 2025)
This research examines the types of satirical language styles and critical reasoning values found in the YouTube video